THE EFFECT OF COMMUNICATION APPROACH ASSISTED AUDIO VISUAL TO IMPROVE THE STUDENTS’ LISTENING ACHIEVEMENT - Zahara Marhamah Siregar (Universitas Islam Sumatera Utara (UISU), 2018)
The objective of this study is to investigate The Effect of Communication Approach Assisted Audio Visual as Media on the Students’ Achievement in listening comprehension. This is an experimental research which applied descriptive quantitative method to describe the result (Syahrum, 2012: 34). This study was conducted at Madrasah Aliyah, islamic bording school of Darul Qur’an. The population of this research was tenth grade. The instruments for collecting data in this research was written test in form multiple choice test, consist of 20 questions. Pre-test and post-test were conducted in both, experimental and control group. The finding showed that the students who are taught by using Communication Approach Assisted Audio Visual as Media got higher score than those who taught by using audio media. The test result showed that there was significant effect of using Communication Approach Assisted Audio Visual as Media on the students’ achievement in listening comprehension which was proven for the result of analysis, was higher than (2,47 > 2,024) at α 0,05, and df 38. It means the hypothesis alternative was accepted.